Developing Efficient Bacterial Consortia to Enhance the Biodegradation of Oil Palm Empty Fruit Bunch (EFB) and Sawdust Lignocelluloses Waste - Joan Alicia, Joseph Blandoi (Universiti Malaysia Sarawak, UNIMAS, 2010)
Empty fruit bunch (EFB) is the lignocellulosic by-product from the oil palm plantation. Without efficient management, EFB could be problematic to the environment. This study aims to develop the microbial consortium for an efficient biodegradation of EFB through windrow composting. Three microbial isolates, Bacillus licheniformis P7, Bacillus amyloliquefaciens UMAS1002, and Pseudomonas aeruginosa IP2 were tested on their ability to degrade EFB based on the parameter time of incubation for 14 days and parameters pH and percentage of inoculums for 10 days. The reducing sugar produced was determined by using Dinitrosalicylic (DNS) method. The best bacterial consortium was inoculated every 10 days of 30-days of EFB composting with uninoculated compost as control. On day 30, the moisture content of inoculated compost is 109.82% with dry mass 0.478 g. The pH is alkaline at 9.68 with bacterial count at 229 × 107 CFU/μl, both lower than control. The reducing sugar produced is 0.477 mg/ml, higher than control and Germination Index (GI) at 1.12 is lower than control. Bacterial consortium AB, consisting of B.amyloliquefaciens UMAS1002 and B.licheniformis P7 is the best microbial consortium developed for EFB degradation. Inoculation of this consortium into EFB compost has less effect in EFB degradation.